Zika, contraception and the non-identity problem - Doolabh, K; Caviola, L; Savulescu, J; Selgelid, M; Wilkinson, D (John Wiley & Sons Ltd, 2017)
The 2016 outbreak of the Zika arbovirus was associated with large numbers of cases of the newlyrecognised Congenital Zika Syndrome (CZS). This novel teratogenic epidemic raises significant ethical and practical issues and highlights a number of challenges for social justice. Many of these arise from strategies used to avoid cases of CZS. While most of the interventions that have been used or proposed in response to Zika are familiar from other mosquito-borne diseases, contraception is one proposed strategy that is less familiar in epidemic control. There are some long-standing ethical and religious objections to the use of contraception. However, using contraception to reduce the burden of CZS has an additional ethical complication: interventions that impact the timing of conception alter which people will exist in the future. This socalled ‘non-identity problem’ potentially has significant social justice implications for evaluating contraception. Some philosophers have argued that the non-identity problem has crucial implications for the duties of health professionals and for intergenerational justice. If this is correct, that may affect our prioritisation of interventions to tackle Zika. In this paper, we combine ethical analysis of the non-identity problem with empirical data from a novel survey about the general public’s moral intuitions. The ethical analysis examines different perspectives on the non-identity problem, and their implications for using contraception in response to Zika. The empirical section reports the results of an online survey of 93 members of the US general public exploring their intuitions about the non-identity problem in the context of the Zika epidemic. Survey respondents indicated a general preference for a person-affecting intervention (mosquito control) over an impersonal intervention (contraception). However, their responses did not appear to be strongly influenced by the non-identity problem. Despite its potential philosophical significance, we conclude from both theoretical considerations and analysis of the attitudes of the community that the non-identity problem should not affect how we prioritise contraception relative to other interventions to avoid CZS. We should focus allocation of healthcare resources to whichever interventions are most cost-effective and practical in addressing the Zika epidemic.